Role of Ciliary Protein Intraflagellar Transport Protein 88 in the Regulation of Cartilage Thickness and Osteoarthritis Development in Mice. Issue 1 (16th December 2021) - Coveney, Clarissa R.; Zhu, Linyi; Miotla‐Zarebska, Jadwiga; Stott, Bryony; Parisi, Ida; Batchelor, Vicky; Duarte, Claudia; Chang, Emer; McSorley, Eleanor; Vincent, Tonia L.; Wann, Angus K. T.
Abstract : Objective: Mechanical and biologic cues drive cellular signaling in cartilage development, health, and disease. Primary cilia proteins, which are implicated in the transduction of biologic and physiochemical signals, control cartilage formation during skeletal development. This study was undertaken to assess the influence of the ciliary protein intraflagellar transport protein 88 (IFT88) on postnatal cartilage from mice with conditional knockout of the Ift88 gene ( Ift88 ‐KO). Methods: Ift88 fl/fl and aggrecanCre ERT2 mice were crossed to create a strain of cartilage‐specific Ift88 ‐KO mice ( aggrecanCre ERT2 ; Ift88 fl/fl ). In these Ift88 ‐KO mice and Ift88 fl/fl control mice, tibial articular cartilage thickness was assessed by histomorphometry, and the integrity of the cartilage was assessed using Osteoarthritis Research Society International (OARSI) damage scores, from adolescence through adulthood. In situ mechanisms of cartilage damage were investigated in the microdissected cartilage sections using immunohistochemistry, RNAScope analysis, and quantitative polymerase chain reaction. Osteoarthritis (OA) was induced in aggrecanCre ERT2 ; Ift88 fl/fl mice and Ift88 fl/fl control mice using surgical destabilization of the medial meniscus (DMM). Following tamoxifen injection and DMM surgery, the mice were given free access to exercise on a wheel. Results: Deletion of Ift88 resulted in progressive reduction in the thickness of the medial tibial cartilage in adolescent mice, as well as marked atrophy of the cartilage in mice during adulthood. In aggrecanCre ERT2 ; Ift88 fl/fl mice at age 34 weeks, the median thickness of the medial tibial cartilage was 89.42 μm (95% confidence interval [95% CI] 84.00–93.49), whereas in Ift88 fl/fl controls at the same age, the median cartilage thickness was 104.00 μm (95% CI 100.30–110.50; P  < 0.0001). At all time points, the median thickness of the calcified cartilage was reduced. In some mice, atrophy of the medial tibial cartilage was associated with complete, spontaneous degradation of the cartilage. Following DMM, aggrecanCre ERT2 ; Ift88 fl/fl mice were found to have increased OARSI scores of cartilage damage. In articular cartilage from maturing mice, atrophy was not associated with obvious increases in aggrecanase‐mediated destruction or chondrocyte hypertrophy. Of the 44 candidate genes analyzed, only Tcf7l2 expression levels correlated with Ift88 expression levels in the microdissected cartilage. However, RNAScope analysis revealed that increased hedgehog (Hh) signaling (as indicated by increased expression of Gli1 ) was associated with the reductions in Ift88 expression in the tibial cartilage from Ift88 ‐deficient mice. Wheel exercise restored both the articular cartilage thickness and levels of Hh signaling in these mice. Conclusion: Our results in a mouse model of OA demonstrate that IFT88 performs a chondroprotective role in articular cartilage by controlling the calcification of cartilage via maintenance of a threshold of Hh signaling during physiologic loading.